KARAKTERISTIK MANISAN NANGKA KERING DENGAN PERENDAMANGULA BERTINGKAT - Imron sohibulloh; Darimiyya hidayati; Burhan Burhan (Agroindustrial Technology, University of Trunojoyo Madura, 2013)
Characteristics by soaking dried candied jackfruit sugar rise. This study examines the rise of sugar immersion or not the characteristics of candied dried jackfruit. Research purposes to determine the concentration of sugar solution and the optimal level of immersion in the manufacture of sugar candied dried jackfruit. The design of the experiment used Completely Randomized Design with two factors: first giving the concentration of sugar solution 3 levels ie 30%, 40% and 50%. The second factor is the level of immersion that for a second soaking soaked in a solution with a higher sugar concentration is 40%, 50% and 60%. Observed variables are organoleptic test, water content, sugar content, sucrose content, and texture analysis. Data were analyzed using ANOVA (Analysis of Variance) Univariate followed by Duncan's test. Research and the level of sugar concentration and immersion significantly affect the color and moisture content. Texture analysis candied dried jackfruit only generate values of hardness and resilience. Highest hardness value sebesar6 candied dried jackfruit, 0120x10 3 on treatment B1A3 (1 time soaking in the sugar concentration of 50%), and the lowest at 5.8347x10 3 treatment B2A1 (2 times soaking in sugar concentration of 40%). Resilience highest value of 0.840 candied dried jackfruit obtained treatment B2A3 (2 times soaking in sugar concentration 60%) and the lowest in treatment B1A3 0.511 (1 time soaking in sugar concentration 50%). Characteristics best candied jackfruit contained on B2A2 treatment (soaking 2 times the sugar concentration of 50%.). B2A2 treatment has karkateristik 17.64% moisture content, sugar content mg/100ml 4.987, 34.0481% yield, hardness 5.9900 x10 3 Ng, resilience 0.540, and the value of a sense of (7.17), aroma (5.27), color (4.73), texture (4.9), and overall preference (4,47).